Pengaruh Lokasi, Fasilitas dan Biaya Pendidikan Terhadap Keputusan Siswa Memilih SMK Mulawarman Balikpapan - Musliati, Sri Indah; Sari, Endah Puspita (Pustaka Galeri Mandiri, 2025)
This study aims to determine the influence of location, facilities, and education costs on students' decisions in choosing SMK Mulawarman Balikpapan. The research method used is a quantitative approach with multiple linear regression analysis techniques. Data were collected through distributing questionnaires to respondents and analyzed using SPSS software version 26. The results of the t-test showed that the location variable had a positive and significant effect on the decision to choose a school (t = 5.657; sig 0.000), as well as the facility variable which showed a positive and significant effect (t = 2.606; sig 0.012). Conversely, the education cost variable had a negative and significant effect on students' decisions (t = -5.167; sig 0.000). The partial coefficient value shows that location contributed the most at 56%, followed by facilities at 21.1%, while education costs had a negative effect at 55.6%. These findings indicate that the more strategic the location and the better the facilities available, the higher the likelihood of students choosing that school. However, the higher the education costs borne, the lower the tendency of students to choose that school.